Bovine Follicular Fluid Derived Extracellular Vesicles Modulate the Viability, Capacitation and Acrosome Reaction of Bull Spermatozoa - Mohammad Mehedi Hasan; Qurat Ul Ain Reshi; Freddy Lättekivi; Janeli Viil; Kasun Godakumara; Keerthie Dissanayake; Aneta Andronowska; Ülle Jaakma; Alireza Fazeli (Biology, 2021)
While follicular fluid (FF) is known to enhance the functional properties of spermatozoa, the role of FF-derived extracellular vesicles (EVs) in this respect is unknown. We hypothesized that bovine FF EVs convey signals to spermatozoa supporting sperm viability, inducing sperm capacitation and acrosome reaction. In this study, the effects of bovine FF EVs on sperm functions are evaluated. Irrespective of the size of the follicles which FF EVs had originated from, they were capable of supporting sperm viability, inducing capacitation and acrosome reaction. These effects were specific to the source of bovine FF EVs, as human-cell-line-derived or porcine FF EVs did not affect spermatozoa viability or induced capacitation and acrosome reaction. A minimum of 5 × 105 EVs/mL was adequate to maintain sperm viability and induce capacitation and acrosome reaction in spermatozoa. Interestingly, with FF EV trypsin treatment, FF EVs lost their ability to support sperm functions. In conclusion, this study demonstrates that bovine FF EVs can support spermatozoa function and may contribute to a favorable periconceptional microenvironment. This is an important aspect of the interactions between different sexes at the earliest stages of reproduction and helps to understand molecular mechanisms modulating processes such as sperm competition and female cryptic choice.